+0  
 
+1
243
2
avatar

One of the roots of the equation kx^2 - 2x - 3 = 0 is -3. Find the value of k.

Guest Mar 19, 2017
 #1
avatar+26742 
+1

We must have:  (x + 3)(kx - a) = 0

 

So:  kx2 + (3k-a)x - 3a = 0. 

 

Compare term by term with kx2 -2x - 3 = 0

 

Clearly a = 1, so 3k - 1 = -2

 

3k = -1

 

k = -1/3

 

.

Alan  Mar 19, 2017
 #2
avatar+12560 
+1

Another method: SUbstitute in -3 fo 'x'  and solve for 'k'

k(9) + 6-3 = 0

k(9) = -3

k = -3/9 = -1/3

ElectricPavlov  Mar 19, 2017

14 Online Users

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.